2022
DOI: 10.1186/s12944-022-01710-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of sitosterolemic children with xanthomas as the first manifestation

Abstract: Background: Sitosterolemia (STSL) is an extremely rare genetic disease. Xanthomas as the first symptom are frequently misinterpreted as familial hypercholesterolemia (FH) in children. Inappropriate treatment may deteriorate the condition of STSL. Objectives: To present the clinical and laboratory characteristics of xanthomatous children diagnosed with sitosterolemia in comparison with childhood FH with xanthomas. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…According to certain research, a juvenile gut may absorb cholesterol at a greater rate than an adult intestine [ 8 ]. Sitosterolemia in children can cause mainly xanthomas [ 9 ], mildly increased cholesterol and LDL-C levels, premature atherosclerotic disease, macrothrombocytopenia, or anemia. There have also been reports of other rare signs, such as growth retardation and thyroid dysfunction, arthritis, liver disease (hepatosplenomegaly with aberrant hepatic function) and cardiac disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to certain research, a juvenile gut may absorb cholesterol at a greater rate than an adult intestine [ 8 ]. Sitosterolemia in children can cause mainly xanthomas [ 9 ], mildly increased cholesterol and LDL-C levels, premature atherosclerotic disease, macrothrombocytopenia, or anemia. There have also been reports of other rare signs, such as growth retardation and thyroid dysfunction, arthritis, liver disease (hepatosplenomegaly with aberrant hepatic function) and cardiac disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the immature intestine may absorb higher amounts of cholesterol than adults [8]. Children with sitosterolemia may be asymptomatic or can mainly manifest as xanthoma [9], slightly elevated cholesterol and LDL-C, premature atherosclerotic disease, and blood system disease (e.g., macrothrombocytopenia, anemia). Other uncommon manifestations, including liver disease (hepatosplenomegaly with abnormal hepatic function), heart disease, arthritis, growth retardation and thyroid dysfunction, have also been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%